Composite material based on natural bamboo wood and having mechanical strength and X / gamma ray shielding performance and preparation method

By mixing high-Z element salts with natural bamboo and adhesives to form a multi-level porous composite material, the problems of high density, softness and easy deformation, and poor interfacial compatibility of existing X/γ ray shielding materials are solved, achieving a lightweight and high-strength X/γ ray shielding effect.

CN120966100APending Publication Date: 2025-11-18SICHUAN UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511244106.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-02
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

Existing X/γ ray shielding materials, such as lead plates, are dense, soft, easily deformable, and highly toxic, making them difficult to use in portable applications. The poor interfacial compatibility between high-Z elements and the matrix material leads to low X/γ ray interaction efficiency.

Method used

Natural bamboo is mixed with high-zir salt and adhesives to form a multi-level porous composite material through electrostatic attraction and coordination. The high-zir element is uniformly loaded on the surface of the bamboo, enhancing interfacial compatibility and mechanical strength.

Benefits of technology

It achieves lightweight and high-strength X/γ-ray shielding performance, improves the interaction frequency and shielding efficiency between photons and high-Z elements, and solves the shortcomings of existing materials in terms of portability and compatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120966100A_ABST
    Figure CN120966100A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a natural bamboo-based composite material with mechanical strength and X / gamma ray shielding performance, which comprises the following steps: step 1, fully mixing and reacting high Z element salt, an adhesive and bamboo to obtain a compound; wherein the mass ratio of the high Z element salt to the adhesive to the bamboo wood is (1-3): (1-100): (1-100); and 2, carrying out hot press molding on the compound obtained in the step 1, and carrying out compression molding to obtain the required composite material, the obtained composite material has good mechanical strength, one or more corresponding high-Z-element salts can be selected according to the characteristics and requirements of application scenes, and the loading capacity, density, thickness and shape of the high-Z-element salts can be adjusted. The cable has the characteristics of light weight, high mechanical strength and strong shielding performance.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of composite materials, and particularly relates to a preparation method of a composite material based on natural bamboo and having mechanical strength and X / γ ray shielding performance. BACKGROUND

[0002] In recent years, high-energy ionizing radiation plays an increasingly important role in many fields, such as disease diagnosis and treatment, industrial flaw detection, mutation breeding, scientific research, etc. Although ionizing radiation provides great help for human development, it also poses a serious threat to human health. Ionizing radiation has high energy and can easily penetrate the human body, causing damage to human organs and causing skin ulcers, DNA damage, cancer and other diseases. Therefore, effective protection against ionizing radiation is a prerequisite for ensuring human life and health and good application of ionizing radiation.

[0003] Ionizing radiation is a form of energy that propagates through electromagnetic waves (such as X-rays, gamma rays) or particle streams (such as alpha particles, beta particles, neutrons), and can ionize atoms or molecules. Ionizing radiation mainly includes alpha rays, beta rays, gamma rays, X-rays and neutron rays. The idea of shielding ionizing radiation is to reduce its intensity by absorbing or scattering radiation energy, and different types of radiation require different types of shielding materials. Alpha radiation has weak penetrating power and can be easily blocked by paper, skin, etc. Beta rays are composed of high-speed electrons or positrons and can be shielded by a few millimeters of plastic, glass or aluminum plate. Gamma rays and X-rays have strong penetrating power and require high-density materials such as lead plates, steel plates or thick concrete for shielding. Neutron rays have extremely strong penetrating power and require materials with high hydrogen content such as water and polyethylene to slow down neutrons, and then use boron compounds or concrete for absorption. Shielding design requires selecting appropriate materials and thicknesses based on the type of radiation to effectively protect the human body and the environment. X / γ rays are the most commonly encountered ionizing radiation in daily life, and effective shielding of X / γ rays is a top priority for ensuring the safety of people's lives and health.

[0004] Lead plates are the most common X / γ ray shielding material, but their high density, softness, deformability and toxicity have presented a series of problems in their application. Due to the high density of lead (11.34 g / cm³), there are difficulties in handling and installing lead plates, especially in portable application scenarios that require X / γ ray shielding. At the same time, lead is a relatively soft metal that is prone to deformation and requires regular maintenance and replacement, which is particularly evident in frequently used scenarios. In addition, lead has high toxicity, and long-term contact or inhalation of lead dust can harm the human body and cause lead poisoning, so strict safety measures are required when using lead plates, which limits the application of lead plates in X / γ ray shielding scenarios.

[0005] At present, the prepared X / γ ray composite shielding material is mostly polymer polymer composite material, which is a high Z element and polymer high polymer blending, and a block material is formed under certain conditions, but this material has the problem of poor interface compatibility between high Z element and matrix material, which makes the dispersion effect of high Z element poor, and reduces the efficiency of X / γ ray and high Z element interaction. Therefore, it is urgent to develop a rigid X / γ ray shielding material with light weight, high mechanical strength and good shielding performance. SUMMARY

[0006] The present application provides a kind of based on natural bamboo material's composite material preparation method with mechanical strength and X / γ ray shielding performance.

[0007] The technical scheme adopted by the present application is: a kind of based on natural bamboo material's composite material preparation method with mechanical strength and X / γ ray shielding performance, comprising the following steps: Step 1: high Z element salt, adhesive, bamboo are fully mixed and reacted to obtain a composite; wherein the mass ratio of high Z element salt, adhesive and bamboo is 1-3:1-100:1-100; Step 2: the composite obtained in step 1 is formed by hot pressing, and the required composite material can be obtained by pressing.

[0008] Further, the Z element in the high Z element salt meets the following conditions: 50≤atomic number≤83.

[0009] Further, the bamboo meets the following conditions: the bamboo is selected from one or more of bamboo fiber, bamboo chips, bamboo block, characterized by three size dimensions of length a, width b and thickness c and its aspect ratio, and the following is the morphology characteristics and size of each form: The fiber is extracted from the bamboo by mechanical separation, chemical treatment or thermochemical treatment, and the fiber is screened to control the size and aspect ratio; the bamboo fiber morphology is in the form of long and thin fiber, and the surface has a micro-rough structure or is surface modified to enhance the interfacial bonding performance of the adhesive; the length a is 0.5mm to 50mm, the width or diameter b is 10um to 500um, the thickness c is less than the width b, and the aspect ratio a / b is 10 to 1000, preferably 50 to 500; The bamboo chips are prepared from bamboo by mechanical or thermal treatment, and the obtained chips are screened to control the particle size distribution; the bamboo chips are in the form of particles, flakes or short strips, the shape includes irregular particles, flakes or short strips, and the surface retains the natural texture of bamboo or is physically or chemically treated to improve the bonding performance; any dimension of the size length a, width b and thickness c of the bamboo chips is 0.1mm to 10mm, the particle size range is 0.1mm to 10mm, and the aspect ratio a / is less than 5, preferably 1 to 3; The bamboo pieces are prepared from bamboo by sawing, planing or splitting, and the obtained bamboo pieces are screened by size or surface treated to meet specific requirements; the bamboo pieces are in the shape of a cuboid, a cube or an irregular block, and the surface is polished, sanded or chemically treated to optimize the bonding interface; the maximum size of any one dimension of the length a, width b and thickness c of the bamboo piece is greater than 10 mm, preferably the length a is 10-500 mm, the width b is 5-200 mm, the thickness c is 2-50 mm, and the length-diameter ratio a / b is 1-20, preferably 2-10.

[0010] Further, the preparation method of the composite in step 1 is: The bamboo is added to a high-Z element salt solution, mixed by one of stirring, overturning oscillation, ultrasonic and shaking bed oscillation, and after sufficient reaction, filtered and dried; Then the adhesive and / or adhesive solution is added, mixed by one of stirring, overturning oscillation, ultrasonic and shaking bed oscillation, and after sufficient reaction, filtered and dried to obtain the required composite.

[0011] Further, the preparation method of the composite in step 1 is: The bamboo is added to an adhesive solution, mixed by one of stirring, overturning oscillation, ultrasonic and shaking bed oscillation, and after sufficient reaction, filtered and dried; Then the high-Z element salt and / or high-Z element salt solution is added, mixed by one of stirring, overturning oscillation, ultrasonic and shaking bed oscillation, and after sufficient reaction, filtered and dried to obtain the required composite.

[0012] Further, the preparation method of the composite in step 1 is: The high-Z element salt and the adhesive are placed in a solvent, mixed thoroughly to obtain a mixed solution; The bamboo is added to the mixed solution, mixed by one of stirring, overturning oscillation, ultrasonic and shaking bed oscillation, and after sufficient reaction, filtered and dried to obtain the required composite.

[0013] Further, the preparation method of the composite in step 1 is: The high-Z element salt, the adhesive and the bamboo are mixed, and one of ball milling, overturning oscillation and high-speed stirring is used for mixing reaction to obtain the required composite.

[0014] Further, the adhesive is selected from one or more of the following categories in any proportion: polyurethane adhesive, polyimide adhesive, polyvinyl alcohol adhesive, polyacrylic acid adhesive, polyester adhesive, epoxy resin adhesive, silicone adhesive, rubber adhesive or bio-based adhesive Furthermore, in step 2, the hot pressing temperature is 50~180℃, the pressure is 0.1~30 MPa, and the pressing time is 0.1~12 h.

[0015] Furthermore, step 2, before hot pressing, also includes a solvent removal process.

[0016] A composite material based on natural bamboo that combines mechanical strength and X / γ ray shielding properties, wherein the thickness of the composite material is 3 to 100 mm.

[0017] The beneficial effects of this invention are: (1) The present invention uses high Z element salt, adhesive and bamboo. The surface of bamboo has abundant active groups, which interact with high Z element salt through electrostatic attraction, coordination and other interactions, and load it onto bamboo. The adhesive achieves high Z element salt efficient bonding at the bamboo fiber interface through electrostatic attraction, coordination and other interactions with bamboo fiber and high Z element salt. (2) The composite material obtained by the present invention uses bamboo with a multi-level porous structure as the substrate, and loads high Z elements to achieve good dispersion of high Z elements, which increases the number and probability of photons colliding in the composite material, and makes the material have strong X / γ ray shielding performance.

[0018] (3) The composite material obtained by the present invention has good mechanical strength, the components interact with each other, and have good interfacial compatibility, which helps to enhance the mechanical strength of the material. Attached Figure Description

[0019] Figure 1 This is a SEM image of the bamboo used in this invention.

[0020] Figure 2 The porosity, total pore area, and average pore diameter of the bamboo fiber, bamboo chips, and bamboo blocks used in this invention.

[0021] Figure 3 The X-ray protection performance test results of bamboo chip-PVA-La composite material and wood chip-PVA-La composite material (5 mm) prepared by the technology used in this invention.

[0022] Figure 4 SEM images of materials obtained in different steps of Embodiment 1 of the present invention.

[0023] Figure 5 This is the EDS-Mapping diagram of the composite material obtained in Example 1 of the present invention.

[0024] Figure 6 The image shown is a SEM image of the composite material obtained in Example 3 of this invention.

[0025] Figure 7This is the EDS-Mapping diagram of the composite material obtained in Example 4 of the present invention.

[0026] Figure 8 This is the EDS-Mapping diagram of the composite material obtained in Example 5 of the present invention.

[0027] Figure 9 To obtain the X-ray protection performance test results of composite materials (5 mm) with different La loading according to the method of Example 1 of the present invention.

[0028] Figure 10 The X-ray protection performance test results of the composite material (5 mm) obtained in Example 3 of the present invention are shown.

[0029] Figure 11 The X-ray protection performance test results of the composite material (5 mm) obtained in Example 8 of the present invention are shown.

[0030] Figure 12 The X-ray protection performance test results of the composite material (5 mm) obtained in Example 9 of the present invention are shown.

[0031] Figure 13 The X-ray protection performance test results of composite materials of different thicknesses obtained according to the method of Example 1 of the present invention are shown.

[0032] Figure 14 The static bending strength of the composite material obtained in Example 11 of the present invention. Detailed Implementation

[0033] The present invention will be further described below with reference to the accompanying drawings and specific embodiments.

[0034] A method for preparing a composite material based on natural bamboo that combines mechanical strength and X / γ-ray shielding properties includes the following steps: Step 1: Thoroughly mix and react the high Z element salt, adhesive, and bamboo to obtain a composite material; wherein the mass ratio of the high Z element salt, adhesive, and bamboo is 1-3:1-100:1-100; the Z element in the high Z element salt meets the following condition: 50≤atomic number≤83.

[0035] Bamboo material is natural bamboo material that meets the following conditions: the bamboo material is selected from one or more of bamboo fiber, bamboo chips, and bamboo blocks, and its characteristic is that it is defined by three dimensional dimensions—length a, width b, and thickness c—and their aspect ratios. The following are the morphological characteristics and dimensions of each form: Bamboo fibers are extracted from bamboo through mechanical separation, chemical treatment, or thermochemical treatment. The fibers are screened to control their size and aspect ratio. The bamboo fibers are long and thin, with a micro-rough surface or surface-modified to enhance their interfacial bonding with adhesives. Their length a is 0.5 mm to 50 mm, width or diameter b is 10 μm to 500 μm, thickness c ≤ width b, and aspect ratio a / b is 10 to 1000, preferably 50 to 500. Bamboo chips are prepared from bamboo through mechanical or heat treatment. The resulting chips are sieved to control particle size distribution. The bamboo chips are in the form of granules, flakes, or short strips, and the shapes include irregular particles, flakes, or short strips. The surface retains the natural texture of the bamboo or is treated physically or chemically to improve adhesion. The dimensions of the bamboo chips, including any one of the length a, width b, and thickness c, are 0.1 mm to 10 mm, the particle size ranges from 0.1 mm to 10 mm, and the aspect ratio a / is less than 5, preferably 1 to 3. Bamboo blocks are prepared from bamboo by sawing, planing, or splitting. The resulting bamboo blocks are size-selected or surface-treated to meet specific requirements. The bamboo blocks are cuboid, cubic, or irregularly shaped, and the surfaces are polished, sanded, or chemically treated to optimize the bonding interface. The maximum dimension of any one of the following dimensions—length a, width b, and thickness c—is greater than 10 mm. Preferably, length a is 10 mm to 500 mm, width b is 5 mm to 200 mm, thickness c is 2 mm to 50 mm, and the aspect ratio a / b is 1 to 20, preferably 2 to 10.

[0036] The complex is prepared by one of the following methods: (1) Add bamboo to a high Z element salt solution and mix it by stirring, turning and shaking, sonication and shaking. After the reaction is complete, filter and dry. Then add it to the adhesive and / or adhesive solution, mix it by stirring, tumbling and oscillating, sonicating and shaking, and allow it to react fully. Filter and dry to obtain the desired composite.

[0037] A high-zir elemental salt is mixed and compounded with bamboo, and the high-zir elemental salt is stably loaded onto the bamboo interface. Then, the compound is mixed and compounded with an adhesive.

[0038] (2) Add bamboo to the adhesive solution and mix it by stirring, turning and oscillating, ultrasonication and shaking. After the reaction is complete, filter and dry. Then add the high-Z elemental salt and / or high-Z elemental salt solution, and mix by stirring, tumbling and oscillating, sonication and shaking. After the reaction is complete, filter and dry to obtain the desired complex.

[0039] First, the adhesive is mixed and compounded with bamboo, and the adhesive is evenly dispersed on the bamboo interface. Then, the compound is mixed and compounded with high Z element salt.

[0040] (3) Place the high Z element salt and adhesive in a solvent and mix thoroughly to obtain a mixture; Bamboo is added to the mixture and mixed using one of the following methods: stirring, tumbling and oscillation, ultrasound, and shaking. After the reaction is complete, the mixture is filtered and dried to obtain the desired composite.

[0041] High-zir salts are mixed with adhesives to form well-dispersed complexes, which are then mixed with bamboo.

[0042] (4) Mix the high Z element salt, adhesive and bamboo, and react them by ball milling, tumbling and oscillation and high speed stirring to obtain the desired composite.

[0043] If a solvent is used in the above composite preparation method, a solvent removal process is required, employing one of the following methods: natural air drying, organic solvent dehydration, high-temperature solvent removal, freeze drying, or vacuum desolventizing. The concentration of the high-zirconium salt solution is 1–50 wt%, with a pH of 2–6.5. The adhesive concentration is 10–40 wt%, with a pH of 4–8.

[0044] The above mixing and reaction are carried out at 30–80 °C for 4–12 h. The adhesive is one or more of polyurethane, polyacetylimide, polyvinyl alcohol, polyacrylic acid, and polylactic acid in any proportion; the bamboo material is one of bamboo chips, bamboo fiber, and bamboo board.

[0045] Step 2: The composite obtained in Step 1 is hot-pressed to obtain the desired composite material. The hot-pressing temperature is 25~180 ℃, the pressure is 0.1~30 MPa, and the pressing time is 0.1~48 h. For testing convenience, the composite material is prepared as a sheet, and the specific shape, thickness, etc. can be determined according to the actual situation.

[0046] Figure 1 The image shows a SEM image of bamboo. As can be seen, bamboo contains a multi-level porous structure, including vascular fiber bundles, thin-walled cell cavities, cell wall pits, and fiber mesopores. This porous structure provides numerous sites for high-Z element loading, facilitating the uniform dispersion of high-Z elements on the bamboo surface. Simultaneously, the numerous cavities help reduce the density of the composite material, thus enabling the construction of a lightweight and efficient X / γ-ray radiation shielding material. More importantly, this multi-level structure can improve the interaction efficiency between photons and high-Z elements, achieving multiple gradient attenuation of photon energy, thereby improving the material's shielding efficiency.

[0047] Figure 2The porosity, total pore area, and average pore diameter of bamboo fiber, bamboo chips, and bamboo blocks were measured by a mercury porosimeter. The figure shows that the porosity of bamboo is as high as 50%, and it also has a high specific surface area and average pore diameter. These characteristics help to efficiently and uniformly load high Z elements, thereby preparing high-performance X / γ-ray radiation protection materials.

[0048] Bamboo is an abundant, green, and sustainable biomass raw material with excellent mechanical properties, widely used in the preparation of composite materials in fields such as construction. Bamboo fiber (BF), abundant in bamboo, consists of bundles, filaments, or flocculent units containing individual fiber cells and aggregates of multiple fiber cells. Compared to other woody fibers, bamboo fiber exhibits strong fiber entanglement and interweaving, high inter-fiber bonding strength, relatively high mechanical strength, and extremely high tensile and specific strength. The characteristics of bamboo fiber give bamboo the advantages of being lightweight and high-strength. On one hand, as a hydrophilic material, bamboo contains a large number of hydroxyl groups, which can coordinate and electrostatically interact with high-zinc element salts, thereby uniformly loading the high-zinc element salts onto the inner and outer surfaces of the bamboo. On the other hand, bamboo has a multi-level structure, which, when used as an X / γ-ray shielding material, can increase the interaction frequency between photons and high-zinc elements, achieving multiple gradient attenuation of photon energy, thus improving the material's shielding efficiency. Therefore, bamboo is an ideal substrate for constructing X / γ-ray shielding materials.

[0049] Figure 3 The figures show bamboo-PVA-La composite material and wood-PVA-La composite material prepared using the same technology. As can be seen from the figures, the X / γ-ray radiation protection material prepared based on bamboo has better X-ray shielding performance than the wood-based material. At an energy of 53 keV, its shielding performance is about 4% higher than that of the X / γ-ray radiation protection material prepared based on wood.

[0050] All components listed below are by weight.

[0051] Example 1 A method for preparing a composite material based on natural bamboo that combines mechanical strength and X / γ-ray shielding properties includes the following steps: Step 1: Weigh 1 part LaCl3·7H2O and dissolve it in 5 parts deionized water and adjust the pH to 10; weigh 1 part polyvinyl alcohol and dissolve it in 20 parts deionized water.

[0052] Two samples of bamboo boards were mixed into the prepared salt solution and agitated at 30 °C for 6 hours. The samples were then filtered and dried at 50 °C. After drying, the samples were placed in a polyvinyl alcohol solution and agitated at 20 °C for 6 hours. The samples were then filtered and dried at 50 °C.

[0053] Step 2: The sample preform is hot-pressed at 110 ℃ and 10 MPa. After cooling and demolding, the natural bamboo-La-polyvinyl alcohol composite material is obtained.

[0054] Figure 4 The image shown is a SEM image obtained in this embodiment. It can be seen from the image that polyvinyl alcohol (PVA) and La... 3+ The resulting complex is uniformly dispersed on the surface of bamboo fiber and has good interfacial compatibility.

[0055] Figure 5 The image shows the EDS-Mapping diagram of the composite material obtained in this embodiment. It can be seen from the diagram that La is uniformly loaded on the surface of the bamboo fiber.

[0056] Figure 9 The X-ray shielding performance of composite materials with different La loadings was tested according to the method in Example 1. The figure shows that the shielding performance improves with increasing La loading, reaching a maximum when the La loading reaches 2 mmol / cm³. 3 At that time, the shielding efficiency of the composite material reached over 60% in the 48 keV energy range.

[0057] Figure 13 The figure shows the X-ray shielding performance test results of composite materials with different thicknesses obtained according to the method of this embodiment. It can be seen from the figure that increasing the thickness can increase its shielding performance to a certain extent. When the thickness of the composite material reaches 12 mm, its shielding efficiency in the 48 keV energy range is close to 100%.

[0058] Example 2 A method for preparing a composite material based on natural bamboo that combines mechanical strength and X / γ-ray shielding properties includes the following steps: Step 1: Weigh out 3 parts Sm(NO3)3·6H2O, 1 part polyvinyl alcohol, and 2 parts bamboo fiber according to the weight ratio, mix them, and ball mill them at 30℃ for 6 hours.

[0059] Step 2: The sample preform is hot-pressed at 110 ℃ and 10 MPa. After cooling and demolding, the natural bamboo-Sm-polyvinyl alcohol composite material is obtained.

[0060] Example 3 A method for preparing a composite material based on natural bamboo that combines mechanical strength and X / γ-ray shielding properties includes the following steps: Step 1: Weigh 3 parts CeCl3·7H2O and mix them with 5 parts deionized water, adjusting the pH to 1; weigh 1 part polyurethane and dissolve it in 20 parts deionized water.

[0061] Two portions of bamboo chips were mixed into the prepared polyurethane solution and agitated at 30 °C for 1 h. The samples were then filtered and dried at 80 °C. After drying, the samples were placed in a salt solution and agitated at 30 °C for 6 h. The samples were then filtered and dried at 50 °C.

[0062] Step 2: The sample preform is hot-pressed at 105 ℃ and 15 MPa. After cooling and demolding, the natural bamboo-Ce-polyurethane composite material is obtained.

[0063] Figure 6 This is a SEM image of the composite material obtained in Example 3 of the present invention. As can be seen from the image, polyvinyl alcohol (PVA) and La... 3+ The resulting complex is uniformly dispersed on the surface of bamboo fiber and has good interfacial compatibility.

[0064] Figure 10 The X-ray protection performance test results of the composite material were obtained as an example. As can be seen from the figure, the shielding efficiency of the composite material in the 48 keV energy range is close to 85% or more, which shows excellent shielding performance.

[0065] Example 4 A method for preparing a composite material based on natural bamboo that combines mechanical strength and X / γ-ray shielding properties includes the following steps: Step 1: Weigh out 3 parts GdCl3·6H2O and 1 part polyacrylic acid according to the weight ratio, mix them with 20 parts deionized water and adjust the pH to 7.

[0066] Two portions of bamboo fragments were mixed into the prepared solution and shaken at 30 °C for 24 h. The samples were then filtered and dried at 45 °C.

[0067] Step 2: The sample preform is hot-pressed at 100 ℃ and 8 MPa. After cooling and demolding, the natural bamboo-Gd-polyacrylic acid composite material is obtained.

[0068] Figure 7 This is the EDS-Mapping diagram of the composite material obtained in Example 4 of the present invention. It can be seen from the diagram that polyacrylic acid and Gd... 3+ The resulting complex is uniformly dispersed on the surface of bamboo fiber and has good interfacial compatibility, which is beneficial to increasing the mechanical properties of the composite material.

[0069] Example 5 A method for preparing a composite material based on natural bamboo that combines mechanical strength and X / γ-ray shielding properties includes the following steps: Step 1: Weigh out 3 parts BaWO4 and 1 part epoxy resin according to the weight ratio and mix them into 30 parts deionized water; Five portions of bamboo powder were mixed into the prepared solution and shaken at 30 °C for 12 h. The samples were then filtered and dried at 60 °C.

[0070] Step 2: The sample preform is hot-pressed at 130 ℃ and 8 MPa. After cooling and demolding, the natural bamboo-Ba / W-polyepoxy resin composite material is obtained.

[0071] Figure 8 The figure shows the EDS-Mapping diagram of the composite material obtained in this embodiment. As can be seen from the figure, the epoxy resin, Ba and W elements are uniformly loaded on the surface of the bamboo, which has good interfacial compatibility and is beneficial to improving the mechanical properties of the composite material.

[0072] Example 6 A method for preparing a composite material based on natural bamboo that combines mechanical strength and X / γ-ray shielding properties includes the following steps: Step 1: Weigh out 2 parts Na2WO4·2H2O, 2 parts polyacrylic acid, and 5 parts bamboo board according to the weight ratio, and shake them at 50 ℃ for 8 h.

[0073] Step 2: The sample preform is hot-pressed at 110 ℃ and 8 MPa. After cooling and demolding, the natural bamboo-La-polyvinyl alcohol composite material is obtained.

[0074] Example 7 A method for preparing a composite material based on natural bamboo that combines mechanical strength and X / γ-ray shielding properties includes the following steps: Step 1: Weigh 1 part LaCl3·7H2O and mix it with 5 parts deionized water, then adjust the pH to 10; weigh 1 part polyvinyl alcohol and dissolve it in 20 parts deionized water.

[0075] Two samples of bamboo boards were mixed into the prepared salt solution and agitated at 30 °C for 6 hours. The samples were then filtered and dried at 50 °C. After drying, the samples were placed in a polyvinyl alcohol solution and agitated at 20 °C for 6 hours. The samples were then filtered and dried at 50 °C.

[0076] Step 2: The sample preform is hot-pressed at 110 ℃ and 10 MPa. After cooling and demolding, the natural bamboo W-polyvinyl alcohol composite material is obtained.

[0077] Example 7 A method for preparing a composite material based on natural bamboo that combines mechanical strength and X / γ-ray shielding properties includes the following steps: Step 1: Weigh 1 part Eu(NO3)3·6H2O and mix it with 300 parts deionized water; weigh 1 part polyacrylic acid and dissolve it in 20 parts acetone.

[0078] Two portions of bamboo fiber were mixed into a prepared suspension (Eu(NO3)3·6H2O suspension), and the mixture was shaken at 30 °C for 6 h. The samples were then filtered and dried at 50 °C. After drying, the samples were placed in a polyacrylic acid solution, shaken at 20 °C for 6 h, and then filtered and dried at 50 °C.

[0079] Step 2: The sample preform is hot-pressed at 105 ℃ and 20 MPa. After cooling and demolding, the natural bamboo-Eu-polyacrylic acid composite material is obtained.

[0080] Example 8 A method for preparing a composite material based on natural bamboo that combines mechanical strength and X / γ-ray shielding properties includes the following steps: Step 1: Weigh 3 parts by weight of La(NO3)36H2O and dissolve it in 300 parts by weight of deionized water; add 5 parts by weight of bamboo chips to the prepared solution. Shake the mixture on a shaker at 30℃ and 180 rpm for 24 h, then filter the sample and dry it at 60℃.

[0081] After drying, add 2 parts of polyvinyl alcohol, vortex for 24 h, then filter the sample and dry at 50 °C.

[0082] Step 2: The sample preform is hot-pressed at 110 ℃ and 5 MPa. After cooling and demolding, the natural bamboo-Yb-polyvinyl alcohol composite material is obtained.

[0083] Figure 11 The X-ray shielding performance test results of the composite material obtained in this embodiment show that the shielding efficiency of the composite material in the 48 keV energy range is close to 60%, indicating good shielding performance. Example 9 A method for preparing a composite material based on natural bamboo that combines mechanical strength and X / γ-ray shielding properties includes the following steps: Step 1: Mix LaCl3·7H2O, 3 parts BiI3, and 2 parts polyvinyl acetate into 10 parts deionized water. Add 5 parts bamboo fiber to the prepared solution and shake on a shaker at 30℃ and 180 rpm for 12 h. Then filter the sample and dry it at 60℃.

[0084] Step 2: The sample preform is hot-pressed at 110 ℃ and 8 MPa. After cooling and demolding, the natural bamboo-La / Bi-polyvinyl acetate composite material is obtained.

[0085] Figure 12The X-ray shielding performance test results of the composite material obtained in this embodiment show that the shielding efficiency of the composite material exceeds 90% in the 48 keV energy range, demonstrating excellent shielding performance. Example 10 A method for preparing a composite material based on natural bamboo that combines mechanical strength and X / γ-ray shielding properties includes the following steps: Step 1: Weigh 10 parts polyvinyl alcohol and 5 parts bamboo board, mix with 100 parts deionized water, and shake on a shaker at 30℃ and 180 rpm for 72 h. Then filter the sample and dry it at 60℃. Add 3 parts PbC4H6O4·3H2O and ball mill for 12 h.

[0086] Step 2: The sample preform is hot-pressed at 110 ℃ and 8 MPa. After cooling and demolding, the natural bamboo-Pb-polyvinyl alcohol composite material is obtained.

[0087] Example 11 A method for preparing a composite material based on natural bamboo that combines mechanical strength and X / γ-ray shielding properties includes the following steps: Weigh 3 parts LuCl36H2O and 2 parts polyacrylic acid and mix them with 10 parts deionized water. Take 10 parts bamboo chips and mix them into the prepared solution. Shake the mixture on a shaker at 30℃ and 180 rpm for 0.5 h. Then filter the sample and dry it at 60℃.

[0088] Step 2: The sample preform is hot-pressed at 150 ℃ and 25 MPa. After cooling and demolding, the natural bamboo-Lu-polyacrylic acid composite material is obtained.

[0089] Figure 14 To obtain the static bending strength of the composite material in this embodiment, it can be seen from the figure that the static bending strength of the composite material gradually increases with the increase of Lu ion loading, reaching a maximum of 40 MPa. This is because Lu ions enhance the internal bonding ability of the composite material by coordinating with the carboxyl groups of polyacrylic acid and the hydroxyl groups on the surface of the main material, thereby enhancing the mechanical properties of the composite material.

[0090] The principle of X / γ-ray shielding is based on two main interactions between X / γ-rays and matter: the photoelectric effect and Compton scattering. High atomic number (Z) elements are particularly important in X / γ-ray shielding because these interactions are closely related to the atomic number of the material. The photoelectric effect is the process by which X / γ-ray photons transfer their energy to the outer electrons of atoms, causing them to escape from their orbits. The probability of the photoelectric effect occurring is proportional to the third to fourth power of the atomic number (Z) of the material. Compton scattering is the process by which X / γ-ray photons collide with free or weakly bound electrons in matter, transferring some energy to the electrons, reducing the photon energy, and changing direction. Its probability is proportional to the electron density of the material. High-Z elements, due to their higher electron density, can more effectively scatter and absorb X / γ-rays. Since the probabilities of both the photoelectric effect and Compton scattering are positively correlated with the atomic number, materials containing high-Z elements have a better shielding effect against X / γ-rays. Bamboo is an abundant source of green and sustainable biomass raw material with excellent mechanical properties, and it is widely used in the preparation of composite materials in fields such as construction. Bamboo fiber (BF), abundant in bamboo, consists of bundles, filaments, or flocculent units comprising individual fiber cells and aggregates of multiple fiber cells. Compared to other woody fibers, bamboo fiber exhibits strong fiber entanglement and interweaving, high inter-fiber bonding strength, and relatively high mechanical strength, possessing extremely high tensile strength and specific strength. These characteristics give bamboo the advantages of being lightweight and high-strength. On one hand, as a hydrophilic material, bamboo contains numerous hydroxyl groups, which can coordinate and electrostatically interact with high-z-element salts, thereby uniformly loading these salts onto the inner and outer surfaces of the bamboo. On the other hand, bamboo possesses a multi-level structure, which, when used as an X / γ-ray shielding material, can increase the interaction frequency between photons and high-z-element elements, achieving multiple gradient attenuations of photon energy and thus improving the material's shielding efficiency.

[0091] The high-Z element salt in the composite material obtained by this invention not only serves as a functional component for X / γ-ray shielding but also as an indispensable adhesive additive in the bonding and molding process of the board. Addressing the problem of high-Z element salt's tendency to crystallize and agglomerate on the substrate surface, this invention provides a method that utilizes the abundant active groups on the bamboo surface to interact with the high-Z element salt through electrostatic attraction and coordination bonding, thereby loading it onto the bamboo. Based on the chemical properties of the bamboo fiber interface and the high-Z element salt, an adhesive with good compatibility with both is selected. During the bonding and molding process of the board, the high-Z element salt is efficiently bonded to the bamboo fiber interface through the interaction of the adhesive or bamboo fiber with the high-Z element salt via electrostatic attraction and coordination bonding. To enhance the attenuation and absorption of X / γ-ray photons in composite materials, bamboo with a multi-level porous structure is used as the substrate. By fully utilizing the pores in the bamboo's cells, vascular bundles, bamboo fiber mesopores, cell walls, and fiber cell walls, high-Z elements are loaded in multiple levels to achieve good dispersion of high-Z elements. This effectively increases the number and probability of photon collisions in the composite material, giving the material strong X / γ-ray shielding performance.

[0092] The composite material obtained by this invention has good mechanical strength. The selected high-Z elemental salt can combine with bamboo and adhesives through multiple interactions, including electrostatic interaction, coordination interaction, and hydrophilic interaction. During the bonding and molding process of the board, the components exhibit good interfacial compatibility, which helps to enhance the mechanical strength of the resulting material. One or more high-Z elemental salts can be selected according to the characteristics and requirements of the application scenario, and the loading, density, thickness, and shape of the high-Z elemental salt can be adjusted. It features light weight, high mechanical strength, and strong shielding performance.

Claims

1. A method for preparing a composite material based on natural bamboo that possesses both mechanical strength and X / γ-ray shielding properties, characterized in that, Includes the following steps: Step 1: Thoroughly mix and react the high Z element salt, adhesive, and bamboo to obtain a composite material; wherein the mass ratio of the high Z element salt, adhesive, and bamboo is 1-3:1-100:1-100; Step 2: The composite obtained in Step 1 is hot-pressed to obtain the desired composite material.

2. The method for preparing a composite material based on natural bamboo that possesses both mechanical strength and X / γ ray shielding properties according to claim 1, characterized in that, The Z element in the high-Z element salt meets the following conditions: 50 ≤ atomic number ≤ 83.

3. The method for preparing a composite material based on natural bamboo that possesses both mechanical strength and X / γ ray shielding properties according to claim 1, characterized in that, The bamboo material meets the following conditions: the bamboo material is selected from one or more of bamboo fiber, bamboo chips, and bamboo blocks, and is characterized by being defined by three dimensional dimensions—length a, width b, and thickness c—and their aspect ratios. The following are the morphological characteristics and dimensions of each form: Bamboo fibers are extracted from bamboo through mechanical separation, chemical treatment, or thermochemical treatment. The fibers are screened to control their size and aspect ratio. The bamboo fibers are long and thin, with a micro-rough surface or surface-modified to enhance their interfacial bonding with adhesives. Their length a is 0.5 mm to 50 mm, width or diameter b is 10 μm to 500 μm, thickness c ≤ width b, and aspect ratio a / b is 10 to 1000, preferably 50 to 500. Bamboo chips are prepared from bamboo through mechanical or heat treatment. The resulting chips are sieved to control particle size distribution. The bamboo chips are in the form of granules, flakes, or short strips, and the shapes include irregular particles, flakes, or short strips. The surface retains the natural texture of the bamboo or is treated physically or chemically to improve adhesion. The dimensions of the bamboo chips, including any one of the length a, width b, and thickness c, are 0.1 mm to 10 mm, the particle size ranges from 0.1 mm to 10 mm, and the aspect ratio a / is less than 5, preferably 1 to 3. Bamboo blocks are prepared from bamboo by sawing, planing, or splitting. The resulting bamboo blocks are size-selected or surface-treated to meet specific requirements. The bamboo blocks are cuboid, cubic, or irregularly shaped, and the surfaces are polished, sanded, or chemically treated to optimize the bonding interface. The maximum dimension of any one of the following dimensions—length a, width b, and thickness c—is greater than 10 mm. Preferably, length a is 10 mm to 500 mm, width b is 5 mm to 200 mm, thickness c is 2 mm to 50 mm, and the aspect ratio a / b is 1 to 20, preferably 2 to 10.

4. The method for preparing a composite material based on natural bamboo that possesses both mechanical strength and X / γ ray shielding properties according to claim 1, characterized in that, The method for preparing the complex in step 1 is as follows: Bamboo is added to a high-Z elemental salt solution and mixed using one of the following methods: stirring, tumbling and oscillation, ultrasound, and shaking. After the reaction is complete, the mixture is filtered and dried. Then add it to the adhesive and / or adhesive solution, mix it by stirring, tumbling and oscillating, sonicating and shaking, and allow it to react fully. Filter and dry to obtain the desired composite.

5. A method for preparing a composite material based on natural bamboo that possesses both mechanical strength and X / γ-ray shielding properties according to claim 1, characterized in that, The method for preparing the complex in step 1 is as follows: Add bamboo to the adhesive solution and mix using one of the following methods: stirring, turning and oscillating, ultrasonication and shaking. After the reaction is complete, filter and dry. Then add the high-Z elemental salt and / or high-Z elemental salt solution, and mix by stirring, tumbling and oscillating, sonication and shaking. After the reaction is complete, filter and dry to obtain the desired complex.

6. The method for preparing a composite material based on natural bamboo that possesses both mechanical strength and X / γ ray shielding properties according to claim 1, characterized in that, The method for preparing the complex in step 1 is as follows: The high-Z elemental salt and adhesive are placed in a solvent and mixed thoroughly to obtain a mixture; Bamboo is added to the mixture and mixed using one of the following methods: stirring, tumbling and oscillation, ultrasound, and shaking. After the reaction is complete, the mixture is filtered and dried to obtain the desired composite.

7. The method for preparing a composite material based on natural bamboo that possesses both mechanical strength and X / γ ray shielding properties according to claim 1, characterized in that, The method for preparing the complex in step 1 is as follows: The desired composite material can be obtained by mixing high-zir elemental salts, adhesives, and bamboo materials, and then using one of the following mixing methods: ball milling, tumbling vibration, or high-speed stirring.

8. A method for preparing a composite material based on natural bamboo that possesses both mechanical strength and X / γ-ray shielding properties according to claim 1, characterized in that, The adhesive is selected from one or more of the following categories and mixed in any proportion: polyurethane adhesives, polyimide adhesives, polyvinyl alcohol adhesives, polyacrylic acid adhesives, polyester adhesives, epoxy resin adhesives, silicone adhesives, rubber adhesives, or bio-based adhesives; the bamboo material is one of bamboo chips, bamboo fiber, and bamboo board.

9. A method for preparing a composite material based on natural bamboo that possesses both mechanical strength and X / γ-ray shielding properties according to claim 1, characterized in that, In step 2, the hot pressing temperature is 50~180℃, the pressure is 0.1~30 MPa, and the pressing time is 0.1~12 h.

10. The method for preparing a composite material based on natural bamboo that possesses both mechanical strength and X / γ-ray shielding properties according to any one of claims 3 to 5, characterized in that, The process of removing solvents before hot pressing in step 2 also includes solvent removal.

11. The composite material based on natural bamboo, possessing both mechanical strength and X / γ-ray shielding properties, obtained by any one of the preparation methods described in claims 1 to 10, is characterized in that... The thickness of the composite material is 3 to 100 mm.